The Effect of Aluminium Surface Treatments on the Bonding Properties of Silica-Modified Epoxy Adhesive Joints: A Statistical Approach - Santos, Francisco M. Dos; Oliveira, Lívia A. de; Bueno, Alysson H. S.; Freire, Rodrigo T. S.; Silva, Leandro José da; Pino, Gilberto García del; Panzera, Tulio H. (Journal of Research Updates in Polymer Science, 2021)
A full factorial design is carried out to investigate the effects of different surface treatments, the inclusion of silica microparticles and the use of wash primer on the apparent shear strength and adherent strength of single-lap aluminium joints. Scanning electron microscopy, surface energy and roughness measurements are performed to characterise the aluminium surface. The results show that the use of wash primer decreases the apparent shear strength of the joints significantly. The cohesive failure of the primer is the main cause of the reduction in strength. On the other hand, the inclusion of 10 wt.% of silica microparticles in the adhesive layers increases the shear strength by 26%. Surfaces treated with NaOH for one minute, without using a wash primer, result in the most resistant joint. In contrast to the apparent shear strength, adherent strength is most effective when only degreasing is considered.